Cyclometallation of a germylene ligand by concerted metalation-deprotonation of a methyl group - Bakthavachalam, K.; Dutta, Sayan; Arivazhagan, C.; Raghavendra, Beesam; Haridas, Anagha; Sen, Sakya S.; Koley, Debasis; Ghosh, Sundargopal (Dalton Transactions, 2018)
The reaction of [CH{(CMe)(2,6-iPr(2)C(6)H(3)N)}(2)]GeCl with LiN(SiMe3)(2) was previously reported, which led to the formation of a hetero-fulvene type germylene, [CH{(CMe)(C?CH2)(2,6-iPr(2)C(6)H(3)N)}(2)]Ge through the deprotonation of the C-H bond from the methyl substituents. In this paper, we attempted the analogous reaction with (Dipp)NCMeCHCOMeGeCl using LiN(SiMe3)(2) which gave rise to a metathesis product, (Dipp)NCMeCHCOMeGeN(SiMe3)(2) (2). However, the reactions of 2 with [M2Cl2(-Cl)(2)((5)-Cp*)(2)] (M = Rh and Ir) resulted in cyclometallated Rh and Ir complexes through the activation of the C-H bond from the germylene ligand. The complexes were characterized by single crystal X-ray analysis, which authenticated the presence of Ge-Rh and Ge-Ir bonds. DFT studies have been performed to understand the mechanism.

Monomeric magnesium catalyzed alkene and alkyne hydroboration - Kumar, Rohit; Dutta, Sayan; Sharma, Vishal; Singh, Praval P.; Gonnade, Rajesh G.; Koley, Debasis; Sen, Sakya S. (Chemistry-A European Journal, 2022)
In this work, two monomeric magnesium alkyl complexes (1 and 2) were prepared using bis(phosphino)carbazole framework and among them 1 has been used as a catalyst for hydroboration of alkenes and alkynes with pinacolborane (HBpin). A broad variety of aromatic and aliphatic alkenes and alkynes were efficiently reduced. Anti-Markovnikov regioselective hydroboration of alkenes and alkynes was achieved, which was confirmed by deuterium-labelling experiments. The work represents the first example of the use of magnesium in homogeneous catalytic hydroboration of alkene with broad substrate scope. Experimental mechanistic investigations and DFT calculations provided insights into the reaction mechanism. Finally, the hydroboration protocol was extended to terpenes.
Keywords: carbazole; Magnesium; monomeric complexes; phosphorous; X-ray Structure